2016
DOI: 10.2134/agronj2016.02.0106
|View full text |Cite
|
Sign up to set email alerts
|

Managing Late‐Season Foliar Nitrogen Fertilization to Increase Grain Protein for Winter Wheat

Abstract: Late‐season applications of foliar N have the potential to increase protein content in hard red winter (HRW) wheat (Triticum aestivum L.), but the optimal N management strategy and economics of this decision have yet to be determined for the U.S. southern Great Plains. This study was conducted to determine the expected net return from HRW wheat managed for enhanced protein and marketed to receive a protein premium. Field experiments were conducted during the 2011 to 2013 harvest years at two Oklahoma locations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 21 publications
4
28
0
Order By: Relevance
“…There was no statistically significant improvement in grain yield with the addition of foliar N for any of the site-years (Tables 4-6). This was expected following similar work conducted by Dick et al (2016) and Woolfolk et al (2002), in which no increases in significant grain yield were observed with postanthesis foliar N applications. No consistent difference was observed in the effect of N rate on grain yield.…”
Section: Grain Yield Responsesupporting
confidence: 68%
See 1 more Smart Citation
“…There was no statistically significant improvement in grain yield with the addition of foliar N for any of the site-years (Tables 4-6). This was expected following similar work conducted by Dick et al (2016) and Woolfolk et al (2002), in which no increases in significant grain yield were observed with postanthesis foliar N applications. No consistent difference was observed in the effect of N rate on grain yield.…”
Section: Grain Yield Responsesupporting
confidence: 68%
“…The ability to successfully increase GPC levels as a result of postanthesis foliar‐applied N has been reported in the literature (Woolfolk et al, 2002; Bly and Woodward, 2003; Dick et al, 2016). Using similar N rates to those used in this study, Woolfolk et al (2002) observed GPC (estimated from grain N data) could be increased on average by about 1.1% and as much as 2.1%.…”
Section: Grain Protein Concentration Responsementioning
confidence: 90%
“…This greater N requirement to maximize GPC as compared to grain yield is widely reported (Goos, Westfall, Ludwick, & Goris, 1982; Hawkesford, 2014; Kelley et al., 1995; Lollato et al., 2019a; Staggenborg et al., 2003; Woodward & Bly, 1998). However, increasing N rates to improve GPC might not be profitable unless price premiums are expected (Dick et al., 2016). Under these conditions, managing N timing arises as an opportunity to improve GPC at similar N rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has shown that late‐season N applications can result in higher protein content, which is supported by Treatment 7 of the current study. It is likely that this effect would be accentuated with the addition of N applications later in the season (Dick et al, 2016; Kratochvil et al, 2005; Woodard and Bly, 1998; Woolfolk et al, 2002). Moreover, where N supply is adequate early in the growing season, N applications at Feekes 6 or later are likely to have little effect on yield (Cassman et al, 1992; Woodard and Bly, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Applying the full rate of UAN mid‐row banded at planting was as economically effective in roughly half the cases, which makes this option a viable alternative, particularly where time constraints exist. Managing N for protein with applications later in the growing season remains physiologically feasible but economically questionable (Dick et al, 2016).…”
Section: Discussionmentioning
confidence: 99%